Performance of hybrid electric vehicle air-conditioning using SiO2/POE nanolubricant - N. N. M., Zawawi; Hamisa, Abdul Hamid; Wan Azmi, Wan Hamzah; Hendrawati, Tri Yuni; Safril, S. (Elsevier, 2023)
The automobile air-conditioning (AAC) system uses the most energy among all auxiliary components in hybrid electric vehicles (HEV) with an electrically-driven compressor (AAC-EDC). Incorporating nanolubricant improves AAC-EDC performance and reduces battery and AAC component size. This study aims to assess the performance of an AAC-EDC system by employing SiO2/POE nanolubricants. The performance of the AAC-EDC was examined using SiO2/POE with a volume concentration of up to 0.01 %, a refrigerant charge of 120–160 g, and a compressor speed of 1200–3840 rpm. The performance of the AAC system was measured by its heat absorption, compressor work, coefficient of performance (COP), and EDC power consumption. The SiO2/POE was stable for 30 days with a zeta potential of 102.5 mV. The SiO2/POE demonstrated superior performance over the pure POE lubricants. The compressor work and power consumption were reduced to 26.17 % and 11.97 %, respectively. The lowest expansion valve discharge temperature of 9.6 °C was achieved at 160 g refrigerant charge and compressor speed of 3840 rpm. The nanolubricant attained the highest COP of 3.36 at 1860 rpm speed and 160 g charge. The SiO2/POE nanolubricant with a volume concentration of 0.01 % is highly recommended for optimal performance in the AAC-EDC system.